A review of recent advances in hydrogen purification for selective removal of oxygen: Deoxo catalysts and reactor systems. (12th July 2022) - Kim, Taejun; Song, Youjung; Kang, Jeongmee; Kim, Seok Ki; Kim, Sungtak
Abstract: As a response to climate change caused by a surge in greenhouse gas emissions and the associated transition to sustainable energy systems, hydrogen (H2 ) is considered as an attracting alternative energy source. In that context, water electrolysis combined with renewable energy source, so called green H2, has been recently receiving great attention from worldwide. However, for stable use of H2 as an energy source in various type of fuel cells to produce electricity, the purity of H2 must not only meet the required level but also be maintained stably. Among possible impurities in the produced H2 steam, oxygen (O2 ) must be controlled below certain level in any circumstances for safety, hence catalytic purification for intensive and selective removal of O2 in H2 steam is nowadays regarded as an essential technology for commercial application of green H2 because of the intermittent nature of renewable energy. Nevertheless, the catalytic purification technology, especially the technology for catalyst and process development, is still in the basic stage, and the reported technologies have not been systemically organized yet. Therefore, this review 1) briefly summarizes the developmental trends and current available technologies of various H2 purification technologies, such as membrane separation, pressure swing adsorption, metal hydride, and cryogenic separation 2) and introduces the developmental of deoxo catalysts and catalytic H2 purification technologies with future research perspectives and suggestions. Highlights: This review summarizes the principles and research trends of catalytic purification of H2 . Catalytic purification can selectively remove O2 from the H2 stream for safe production of green H2 . Future research directions for deoxo catalysts and catalytic purification are discussed.